A non-invasive method for the diagnosis of upper GI diseases - Barchi, Alberto; Miraglia, Chiara; Violi, Alessandra; Cambiè, Ginevra; Nouvenne, Antonio; Capasso, Mario; Leandro, Gioacchino; Meschi, Tiziana; de' Angelis, Gian Luigi; Di Mario, Francesco (Acta Biomedica Atenei Parmensis, 2018)
Upper-GI diseases are one of the most relevant issue in primary care. Nowadays they are still responsible for about 100 million ambulatory care visits only in the US. The diagnosis of almost every upper-GI condition is still deputed to invasive tests such as upper gastrointestinal endoscopy, gastroesophageal manometry or radiography. The possibility of analysing serum markers like Pepsinogens I and II, produced by gastric mucosa, in order to assess the functional characteristics of the upper GI tract has spread itself since the 80’s especially in the diagnosis of peptic ulcer. The discovery of Helicobacter pylori by Marshall and Warren in 1983 and the scientific consecration of its role in the pathogenesis of gastric cancer and peptic ulcer (crystallized in Peleo Correa’s Cascade, 1992), led to an increase importance of non-invasive tests, raising the attention towards the assessment of both immunoglobulins anti-H.p. and Gastrin hormone produced by antral G cells, as an implementation of the panel of gastric markers. This narrative review aims to analyze the huge landscape of non-invasive tests for diagnosis of GI diseases, studying the literature of the recent years.